Explorasi Moderasi Agama melalui Intensitas Kegiatan Jurnalistik Santri - Farhan Farhan; Zulfa Nouruz Zaman L Malik; Mochammad Farid Nuruz Zaman; Zulfa Ihlas Mubaroq (International Consortium of Islamic Researchers (ICONIRs) CV. Branded Tech Indonesia, 2024)
This study examines the construction of multicultural education in enhancing students’ tolerance at Pondok Pesantren Asy-Syarify Pandanwangi Lumajang. Using a post-positivist approach with an interpretative method, the research analyzes the implementation of multicultural values and identifies supporting and inhibiting factors. The findings indicate that values such as equality, justice, tolerance (tasamuh), deliberation (musyawarah), and brotherhood (ukhuwah) have been effectively integrated into the curriculum, extracurricular activities, and pesantren culture. However, challenges remain, including limited media resources and individual students' attitudes toward diversity. This study concludes that the construction of multicultural education in the pesantren plays a crucial role in fostering students’ tolerance. Despite existing obstacles, the pesantren continues to strive toward creating an inclusive and harmonious environment.